When entering coefficients to balance equations, recall that just writing the symbol implies "1." Therefore, if a coefficient of "1" is required, choose "blank" for that box. Balance the following reaction. MgCl2 + AgNO3 → AgCl + Mg(NO3)2

Respuesta :

znk

The balanced equation is MgCl₂ +2AgNO₃ ⟶ 2AgCl + Mg(NO₃)₂

Step 1. Start with the most complicated-looking formula [Mg(NO₃)₂].

Put a 1 in front of it and balance its atoms.

MgCl₂ +AgNO₃ ⟶ AgCl + 1Mg(NO₃)₂

Step 2. Balance Mg.

1MgCl₂ +AgNO₃ ⟶ AgCl + 1Mg(NO₃)₂

Already balanced —1 atom each side.

Step 3. Balance N.

We have 2 N on the right-hand side and 1 N on the left. We need 2 N on the left. Put a 2 in front of AgNO₃.

1MgCl₂ +2AgNO₃ ⟶ AgCl + 1Mg(NO₃)₂

Step 4: Balance O

Done. We have 6 O on the left and 6 O on the right.

Step 5. Balance Ag.

We have 2 Ag on the left, so we need 2 Ag on the right. Put a 2 in front of AgCl.

1MgCl₂ +2AgNO₃ ⟶ 2AgCl + 1Mg(NO₃)₂

The balanced equation is

MgCl₂ +2AgNO₃ ⟶ 2AgCl + Mg(NO₃)₂

Answer:

1,2,2,1

Explanation: